2021
DOI: 10.1155/2021/6284987
|View full text |Cite
|
Sign up to set email alerts
|

Various Forms of Tuberculosis in Patients with Inflammatory Bowel Diseases Treated with Biological Agents

Abstract: Although there are undeniable advantages of treatment of the inflammatory bowel diseases, Crohn’s disease, and ulcerative colitis, with biological agents, the increased susceptibility to tuberculosis should not be ignored. Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis complex which includes M. tuberculosis, M. bovis, and M. africanum. Primary tuberculosis is uncommon in the setting of inflammatory bowel disease: reactivation of latent tuberculosis is of greater concern. Consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The association between PTB and inflammatory bowel disease (IBD) was also reported in a recent study. Krusinski et al found that biological agents for IBD may increase the susceptibility to TB [ 29 ]. Additionally, we found that some comorbidities demonstrated age discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…The association between PTB and inflammatory bowel disease (IBD) was also reported in a recent study. Krusinski et al found that biological agents for IBD may increase the susceptibility to TB [ 29 ]. Additionally, we found that some comorbidities demonstrated age discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…While anti-TNF can be used for severe ulcerative colitis treatment, there’s a risk of recurrence if it is discontinued [ 25 ]. Furthermore, biologic agents, exemplified by anti-TNF drugs, introduce an elevated vulnerability to infections among UC patients, concurrently posing risks of diverse tuberculosis manifestations [ 26 , 27 ]. Notwithstanding the reduction in surgical interventions post-biologic usage, the lingering disease susceptibility coupled with postoperative complications remains a persistent concern [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of immunomodulators is not only toxic, but one case follow-up showed possible transformation into high-grade squamous intraepithelial lesions, which are precancerous [25]. Biologics such as anti-TNF drugs not only increase the risk of infection in UC patients, but may also present with various types of TB [26,27]. Although surgical treatment is reduced after the use of biologics, the risk of disease remains high and postoperative complications continue to plague [28].…”
Section: Discussionmentioning
confidence: 99%